Taxonomic Studies On The Macrofungi Growing In Eucalyptus Forests In Mugla Province - Güler Ünal; Aziz Türkoğlu; Mehrican Yaratanakul Güngör (Turkish Journal of Agriculture: Food Science and Technology, 2016)
In this study macrofungi specimens have been collected from Eucalyptus forests in Muğla district (Ula, Köyceğiz, Marmaris, Dalaman, Fethiye) in the years of 2013-2014. As a result of the field and fungarium studies, Totally 30 taxa belonging to 2 classes and 14 families have been identified. 2 of these taxa belong to Ascomycota, and the other 28 taxa were belong to Basidiomycota.